Effects of Antagonists on Mycotoxins of Seedborne Fusarium spp. in Sweet Corn - Mary E. Ridout; Bruce Godfrey; George Newcombe (Toxins, 2019)
Fusarium species coexist as toxigenic, systemic pathogens in sweet corn seed production in southwestern Idaho, USA. We hypothesized that fungal antagonists of seedborne Fusarium would differentially alter production of Fusarium mycotoxins directly and/or systemically. We challenged the Fusarium complex by in vitro antagonism trials and in situ silk and seed inoculations with fungal antagonists. Fungal antagonists reduced growth and sporulation of Fusarium species in vitro from 40.5% to as much as 100%. Pichia membranifaciens and Penicillium griseolum reduced fumonisin production by F. verticillioides by 73% and 49%, respectively, while P. membranifaciens and a novel Penicillium sp. (WPT) reduced fumonisins by F. proliferatum 56% and 78%, respectively. In situ, pre-planting inoculation of seeds with Penicillium WPT systemically increased fumonisins in the resulting crop. Morchella snyderi applied to silks of an F1 cross systemically reduced deoxynivalenol by 47% in mature seeds of the F2. Antagonists failed to suppress Fusarium in mature kernels following silk inoculations, although the ratio of F. verticillioides to total Fusarium double with some inoculants. Fusarium mycotoxin concentrations in sweet corn seed change systemically, as well as locally, in response to the presence of fungal antagonists, although in Fusarium presence in situ was not changed.